(3GdeGFIs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3bGd CHh Sgd (B: (3gPG gh GdcJGH GdSHYhf ef cJHfG ai UfGYI GdWH hbUQfG ajg ai YdGL GeQGV GdCSfGf s
(3BNQgG (B:s
(3hjNaa ai GdXdGe hHQaY GdTGbI ef bOQ GdYOS hjSJYed efg LRA Je GdcJGH s
(3bWYI ef fSNI KGfjI cJHJ SfI (B990(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B162 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1576s
Keywords: (3GdWHs